JIKA RESPONDEN MENIPU, APAKAH HASIL PENGUKURAN OLEH SKALA MASIH ANDAL? - Wahyu Widhiarso (MANASA, 2012)
The aim of this study is to explore the impact of faking responses on measurement reliability of psychological scales. Experiments were conducted on 200 subjects who were asked to complete Five Factors Personality Scale (BFI-44) with two different instructions. First instruction asked subjects to respond within a neutral condition, whereas second instruction asked subjects to respond to the scale when they are participating in employment selection (motivated conditions). Comparisons of alpha coefficient between these conditions suggest that faking responses does not interfere measurement reliability. Pure score proportion on observed score was unaffected by presence of faking responses.However, using the state-trait model, it is found that untainted score proportion on observed scores are more related to state score compared to the trait score as main measurement target. Results of separated analysis model toward personality factors shown that Agreeableness and Openness are factors which were relatively resistant to faking responses. Trait score proportion of these factors still large although faking responses were presence.